2010
DOI: 10.1097/brs.0b013e3181c85151
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validation of the DASH and the QuickDASH in Comparison to Neck-Specific Scales in Patients With Neck Pain

Abstract: Though the QuickDASH reported higher disability compared to the full DASH in this patient group, high correlation between the QuickDASH and the NDI and agreement between both versions of the DASH provide preliminary evidence that the QuickDASH can be used to measure upper extremity disability in patients with neck pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 46 publications
(36 reference statements)
3
44
1
Order By: Relevance
“…4,27,39 Our data agreed in terms of the direction of this bias (QuickDASH giving higher scores), but suggested that the potential bias was relatively small (1-3 points). The frequency distribution graph of difference between the QuickDASH and DASH indicates that score differences usually are less than 5 points, although our limits of agreement illustrated that it was a sizable difference in some patients.…”
Section: Discussionsupporting
confidence: 55%
“…4,27,39 Our data agreed in terms of the direction of this bias (QuickDASH giving higher scores), but suggested that the potential bias was relatively small (1-3 points). The frequency distribution graph of difference between the QuickDASH and DASH indicates that score differences usually are less than 5 points, although our limits of agreement illustrated that it was a sizable difference in some patients.…”
Section: Discussionsupporting
confidence: 55%
“…Although studies have shown that the full-length questionnaire provides more specific and accurate results, 18 numerous reports also indicate that the QuickDASH instrument can be used instead of the DASH questionnaire, with similar precision in upper extremity disorders. 16,[19][20][21] Additional studies have shown the independent responsiveness, validity, and reliability of the QuickDASH 22-26 for various upper extremity disorders.…”
Section: Methodsmentioning
confidence: 99%
“…The scores on the NDI and DASH showed good correlation (whole population correlation r = 0.51). Higher levels of correlation have been reported in the literature (0.7-0.8) (McLean et al, 2011;Mehta et al, 2010;Osborn and Jull 2013) indicating a substantial link between upper limb function and neck pain.…”
Section: Discussionmentioning
confidence: 67%
“…Osborn and Jull (2013) state that up to 80% of patients report upper limb activities aggravating to their neck pain. Other studies have reported a high correlation (r = 0.67-0.83) between neck disability (evaluated using the Neck Disability Index (NDI) and the Northwick Park Neck Pain Questionnaire (NPQ)) and disability of the upper limb (evaluated using the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire (Huisstede et al, 2009;Mehta et al, 2010;Osborn and Jull 2013) indicating a relationship between neck pain and upper limb disability. Although the exact mechanism between impaired upper limb function and neck pain has not been extensively researched, studies investigating the efficacy of exercise for the treatment of neck pain and headaches usually include shoulder girdle and upper limb exercises in their exercise protocols (Amorim et al, 2014;Ang et al, 2009;Bronfort et al, 2001;Franca et al, 2008;Jull et al, 2002;Kay et al, 2012;Varatharajan et al, 2016).…”
Section: Study 1 (Chapter 3)mentioning
confidence: 99%
See 1 more Smart Citation